Association between Pain and Frequent Physical Exercise among Adults in the United States: A Cross-Sectional Database Study - David R. Axon; Taylor Maldonado (MDPI AG, 2023)
Pain affects over 20% of United States adults, and less than 50% of United States adults participate in frequent physical exercise. This cross-sectional database study included 13,758 United States adults aged >18 years from the 2020 Medical Expenditure Panel Survey (MEPS) and analyzed the association between severity of pain (independent variable) and frequent physical exercise (dependent variable), adjusting for demographic, economic, limitation, and health variables using multivariable logistic regression. The study showed 50.3% of adults report frequently exercising. Only 37.1% of adults reported experiencing pain of any degree, with a majority of them experiencing little pain. In the adjusted model, extreme pain vs. none, quite a bit of pain vs. none, Hispanic vs. non-Hispanic ethnicity, having a functional limitation vs. no limitation, and being overweight/obese vs. not being obese/overweight were associated with lower odds of reporting doing frequent physical exercise. Meanwhile, being ≥65 or 40-64 vs. 18-39 years of age, male vs. female, white vs. not white race, private or public vs. no health coverage, and good vs. poor general health were associated with greater odds of reporting doing frequent physical exercise. These variables associated with frequent physical exercise should be considered in future work when designing health interventions.